Literature Review: Bahan Alam yang Berpotensi sebagai Antidiabetes: Literature Review: Natural Ingredients that Have Potential as Antidiabetic - Novalinda Novalinda; Mukti Priastomo; Laode Rijai (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Antidiabetes is a treatment that is currently much needed for diabetics, because the cost of treatment is getting higher, so it is recommended to use herbs as an alternative treatment. This study aims to determine natural ingredients that have the potential as antidiabetic. The method used is a systematic review by collecting, analyzing and summarizing 25 journals with the publication year 2016-2021 with keywords namely Antidiabetes, Natural Ingredients, and In Vivo. The results of the journal analysis are Beluntas leaves 0.9 mg/20 gBW, Kecombrang leaves 100 mg/kgBW, Keji Beling leaves 300 mg/kgBW, Kembang Bulan leaves 5.14 ml/200gBW, Kenikir leaves 1400 mg/200gBW, Mango leaves 105 mg /kgBW, Pucuk Merah leaves 100 g/kgBW, Rambutan leaves 50 mg/kgBW, Sambiloto leaves 40 mg/kgBW, Breadfruit leaves 600 mg/kgBW, Avocado seeds 150 mg/kgBW, Kebiul seeds 51mg/20gBW, Green Coffee Beans Arabica 400 mg/kgBW, Dates seeds 10 mL/day, Pumpkin seeds 720 mg/kgBW, Okra seeds 5,46 mg/gBW, Areca seeds 750 mg/kgBW, Buni bark 200 mg/kgBW, Faloak bark 150 mg /kgBW, Surian bark 150 mg/kgBW, Bilimbi fruit 750 mg/kgBW, Purple Sweet Potato fruit 150 mg/kgBW, Papaya flower 200 mg/kgBW, Pineapple peel 250 mg/kgBW and Black Garlic tuber 300 mg/kgBW with this optimal dose can reduce blood glucose levels.